1992
DOI: 10.1080/01652176.1992.9694330
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and clinicochemical blood profiles in slaughter pigs

Abstract: SUMMARYIn a cohort study, 40 pig finishing herds were selected twenty pig herds with a low and twenty pig herds with a high prevalence of several pathological lesions recorded at slaughter in a six-month period before the start of the study. Blood samples were taken from 20 pigs per herd at the end of the finishing period to investigate haematological and clinicochemical profiles. There was only a significant difference in serum albumin concentration between the low and high lesion prevalence groups. There wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
5
9
0
Order By: Relevance
“…In pigs, albumin is considered one of the most important predictors of performance, especially average daily gain and feed conversion ratio [48]. In accordance with these finding and Elbers et al [49], our study demonstrated that piglets with higher ADFI and ADG had higher albumin levels. Moreover, in our study, insulin was significantly higher in the TRIB group compared to the CTRL group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In pigs, albumin is considered one of the most important predictors of performance, especially average daily gain and feed conversion ratio [48]. In accordance with these finding and Elbers et al [49], our study demonstrated that piglets with higher ADFI and ADG had higher albumin levels. Moreover, in our study, insulin was significantly higher in the TRIB group compared to the CTRL group.…”
Section: Discussionsupporting
confidence: 91%
“…Albumin is strongly related to insulin synthesis [50,51] and it is well known that insulin is associated with muscle protein synthesis [52,53]. Moreover, the data in our study were in the physiological range [49]. The same author demonstrated that piglets with higher serum albumin had also higher daily weight gain, in line with our study.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, leukocytes were increased and Hg and albumin concentrations were reduced among NANI pigs, suggesting that these pigs may have been experiencing some form of inflammatory response. Albumin concentrations have also been shown to be reduced in pigs with abscesses Elber et al, 1992). Changes in leukocyte percentages and albumin concentrations in NANI pigs suggest that these pigs were experiencing some sort of active infection whether due to viral infection or inflammation which may be a contributing factor for them going down during transport.…”
Section: Discussionmentioning
confidence: 95%
“…In general, it is known that the reference values described in the literature differ considerably, primarily due to variation in age, breed, husbandry, housing conditions (SPF), and laboratory methods used for blood analysis. Additionally, stress and the genetic composition of the different minipig breeds may cause differences in blood and serum parameters [17,18,19]. …”
Section: Discussionmentioning
confidence: 99%